A code comparison exercise within the European project RODOS: harmonising domestic and reference tools. (1st January 2002) - Vamanu, D.; Mateescu, G.; Berinde, A.; Slavnicu, D.; Acasandrei, V.
One term of reference for validly teaming up with Real Time Online Decision Support System for Off-Site Nuclear Emergencies in Europe (RODOS) is to contribute research initiatives geared towards emulating the RODOS functions on novel conceptual pathways; expand the system's coverage of issues that are relevant in nuclear crisis management and bring in domestic perspectives on how the system may best respond to local needs and constraints in each and every national - i.e., legal, managerial, logistic and cultural - environment. The paper reports results of a comparison between selected RODOS applications on simulated abnormal nuclear events and the concurrent application of a resident software package developed to emulate RODOS-wise functions, at IFIN-HH Bucharest. The reproducible similarity pattern obtained in data distributions provide for simple normalising procedures that may make domestic Decision Support System (DSS) facilities useful as both practical tools and factors promoting emergency preparedness awareness, during the interim time lapse until the full development and deployment of RODOS as a reference DSS in Europe.